THE IMPACT OF EXCHANGE RATE VOLATILITY ON THE MACRO ECONOMIC VARIABLES IN NIGERIA - Danmola, Rasaq Akonji (European Scientific Journal, ESJ, 2013)
The study analyses the impact of exchange rate volatility on Macroeconomic variables and with the help of Correlation Matrix, Ordinary Least Square (OLS) and Granger Causality test, the findings of the study shows that exchange rate volatility has a positive influence on Gross Domestic Product, Foreign Direct Investment and Trade Openness, but with negative influence on the inflationary rate in the country. It was suggested by the author, that the need country to improve their revenue base in term of increasing number of items meant for export and reduce over reliance on petroleum sector and also to reduce the importation of non essential items, so as improve their term of trade. Also increase in domestic production will reduce the problem caused by exchange rate volatility.